Expanding structural diversity of 5′-aminouridine moiety of sansanmycin via mutational biosynthesis - Lu, Yuan; Li, Yihong; Fan, Jiahui; Li, Xingxing; Sun, Hongmin; Wang, Lifei; Han, Xingli; Zhu, Yuting; Zhang, Tianyu; Shi, Yuanyuan; Xie, Yunying; Hong, Bin (Frontiers in Bioengineering and Biotechnology, 2023)
Sansanmycins represent a family of uridyl peptide antibiotics with antimicrobial activity specifically against Mycobacterium tuberculosis (including drug-resistant M. tuberculosis) and Pseudomonas aeruginosa. They target translocase I (MraY) to inhibit bacterial cell wall assembly. Given the unique mechanism of action, sansanmycin has emerged as a potential lead compound for developing new anti-tuberculosis drugs, while the 5'-aminouridine moiety plays a crucial role in the pharmacophore of sansanmycin. For expanding the structural diversity of the 5'-aminouridine moiety of sansanmycin through biosynthetic methods, we firstly demonstrated that SsaM and SsaK are responsible for the biosynthesis of the 5'-aminouridine moiety of sansanmycin in vivo. Using the ssaK deletion mutant (SS/KKO), we efficiently obtained a series of new analogues with modified 5'aminouridine moieties through mutational biosynthesis. Based on molecular networking analysis of MS/MS, twenty-two new analogues (SS-KK-1 to -13 and SS-KK-A to -I) were identified. Among them, four new analogues (SS-KK-1 to -3 and SS-KK-C) were purified and bioassayed. SS-KK-2 showed better antibacterial activity against E. coli ΔtolC than the parent compound sansanmycin A. SS-KK-3 showed the same anti-TB activity as sansanmycin A against M. tuberculosis H37Rv as well as clinically isolated, drug-sensitive and multidrug-resistant M. tuberculosis strains. Furthermore, SS-KK-3 exhibited significantly improved structural stability compared to sansanmycin A. The results suggested that mutasynthesis is an effective and practical strategy for expanding the structural diversity of 5'-aminouridine moiety in sansanmycin.